Calculation studies of heat transfer in the flow of nanofluids - E. N. Slobodina; I. A. Stepashkin; D. V. Kovalenko; A. G. Mikhailov; E. A. Rogachev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This research delves into the study of heat transfer in nanofluids, which are specialized fluids containing nanoparticles. The investigation focuses on understanding crucial factors affecting heat transfer in nanofluids, such as thermal conductivity, viscosity, flow patterns, and density. Both experimental and computational methods are employed to explore how various nanofluid compositions perform in different scenarios. The outcomes of this study contribute to an improved comprehension of nanofluid behavior and its potential applications in enhancing heat transfer processes